The value of psychological treatment for borderline personality disorder: Systematic review and cost offset analysis of economic evaluations. - Denise Meuldijk; Alexandra McCarthy; Marianne E Bourke; Brin F S Grenyer (PLoS ONE, 2017)
AIM:Borderline Personality Disorder (BPD) is a common mental health condition with high patterns of service utilisation of inpatient and community treatment. Over the past five years there has been significant growth in research with economic data, making this systematic review a timely update. METHODS:Empirical studies written in English or German, published up to December 2015, and cited in major electronic databases were examined using the PRISMA systematic review method. Papers were included that had one of the following: data related to cost of BPD to society, the individual, the carer or families; cost benefits of interventions. Reported cost data were inflated to the year 2015 and converted into US- dollars (USD $) using purchasing power parities. RESULTS:We identified 30 economic evaluations providing cost data related to interventions for BPD across 134,136 patients. The methodological quality was good, almost all studies fulfilled ≥ 50% of the quality criteria. The mean cost saving for treating BPD with evidence-based psychotherapy across studies was USD $2,987.82 per patient per year. A further mean weighted reduction of USD $1,551 per patient per year (range $83 - $29,392) was found compared to treatment as usual. Evidence-based psychological treatment was both less expensive as well as more effective, despite considerable differences in health cost arrangements between individual studies and countries. Where it was able to be calculated, a significant difference in cost-savings between different types of evidence-based psychotherapies was found. DISCUSSION:Individuals with BPD consistently demonstrate high patterns of service utilization and therefore high costs. The findings of this review present a strong argument in favour of prioritizing BPD treatments in reimbursement decisions, both for the affected individual and the family. The provision of evidence based treatment, irrespective of the type of psychological treatment, may lead to widespread reductions in healthcare costs.